A novel prognostic model for Japanese patients with newly diagnosed bone‐metastatic hormone‐naïve prostate cancer. Issue 2 (18th September 2020) - Miyoshi, Yasuhide; Yasui, Masato; Yoneyama, Shuko; Kawahara, Takashi; Nakagami, Yoshihiro; Ohno, Yoshimasa; Iizuka, Junpei; Tanabe, Kazunari; Hashimoto, Yasunobu; Tsumura, Hideyasu; Tabata, Ken‐ichi; Iwamura, Masatsugu; et al.
Abstract: Objectives: To evaluate the prognosis of newly diagnosed patients with metastatic hormone‐naïve prostate cancer (mHNPC) and develop a novel prognostic model based on ChemoHormonal Therapy Versus Androgen Ablation Randomized Trial for Extensive Disease in Prostate Cancer (CHAARTED) risk classifications. Patients and methods: We retrospectively analyzed the data of 578 newly diagnosed mHNPC patients initially treated with androgen deprivation therapy. We evaluated three clinical factors, namely, CHAARTED risk classifications (high‐volume disease [HVD] vs low‐volume disease [LVD]), Gleason scores (GS, 9‐10 vs ≤8), and hemoglobin (Hb, ≤13.0 g/dL vs >13.0 g/dL), for their prognostic potential in predicting time to castration‐resistant prostate cancer (TTC) and overall survival (OS) of mHNPC patients by multivariate analysis. Moreover, we developed a novel prognostic model that consisted of significant prognostic factors. Results: Of the entire cohort, the median TTC and OS values were 18.3 and 67.5 months, respectively. HVD, GS 9‐10, and Hb ≤13.0 g/dL were independent poor prognostic factors for both TTC and OS. We developed a novel prognostic model which could stratify mHNPC patients into four risk groups according to the numbers of poor prognostic factors: group 1, LVD with low‐risk (LVD patients without GS 9‐10 and Hb ≤13.0 g/dL); group 2, LVD with high‐risk (LVD patients with GS 9‐10, Hb ≤13.0 g/dL, or both); group 3, HVD with low‐risk (HVD patients without GS 9‐10 with or without Hb ≤13.0 g/dL); and group 4, HVD with high‐risk (HVD patients with GS 9‐10 with or without Hb ≤13.0 g/dL). The median TTC and OS of groups 1, 2, 3, and 4 were 124.8, 36.4, 17.9, and 11.2 months, and 117.2, 94.2, 67.9, and 46.2 months, respectively. A significant difference in TCC and OS was found between all groups. Conclusion: We developed a prognostic model for mHNPC patients that consisted of CHAARTED risk classifications, GS, and Hb. Our prognostic model could significantly stratify the prognosis of patients with LVD and HVD into two groups each. This model might be a good reference for shared decision making between patients and physicians on the initial treatment for mHNPC.